Cellulose - Rodríguez Pascual, Alejandro; Eugenio Martín, María E. (IntechOpen, 2019)
Cellulosic fibers are becoming increasingly important in many industrial sectors. Indeed, their availability, low cost, and durability make them suitable for application in various fields. This book presents important information about the structure of cellulose as well as its uses and applications. Topics covered include: the dynamic modeling of cellulose industry systems for biofuels in the United States; the integration of alternative raw materials to wood in biorefinery processes; the influence of size classification on the properties of cellulose materials; the chemistry of cellulose, its extraction, and its properties; cellulases; and enzymatic treatments for producing surface activation on cellulosic fibers.